2022
DOI: 10.1002/pa.2838
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between corporate social responsibility, corporate reputation and brand equity in Indian banking industry

Abstract: This study is an attempt to explain the relationship between corporate social responsibility (CSR), corporate reputation, and brand equity in India's banking sector. The study uses Carroll's Pyramid of CSR and the 'triple bottom line concept' as the theoretical bases for proposing a conceptual model. The data pertaining to 482 saving bank customers were analysed using structural equation modelling for this study. The integrated effect of CSR and corporate reputation on brand equity has been examined using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 128 publications
0
1
0
Order By: Relevance
“…Similarly, the second hypothesis, which posited that CSR impacts firm reputation, was also supported by the study's findings. This result is consistent with previous studies (Gulzar et al, 2018;Melero-Polo & López-Pérez, 2017;Forcadell & Aracil, 2017;Yan et al, 2022;Brammer and Pavelin, 2016;Gardberg et al, 2019;Khan et al, 2020a;Aggarwal & Saxena, 2023;Zhao et al, 2021;Cabrera-Luján et al, 2023) and underscores the significance of CSR in shaping a company's reputation. These findings are also aligned with stakeholder theory.…”
Section: Data Reliability Testsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the second hypothesis, which posited that CSR impacts firm reputation, was also supported by the study's findings. This result is consistent with previous studies (Gulzar et al, 2018;Melero-Polo & López-Pérez, 2017;Forcadell & Aracil, 2017;Yan et al, 2022;Brammer and Pavelin, 2016;Gardberg et al, 2019;Khan et al, 2020a;Aggarwal & Saxena, 2023;Zhao et al, 2021;Cabrera-Luján et al, 2023) and underscores the significance of CSR in shaping a company's reputation. These findings are also aligned with stakeholder theory.…”
Section: Data Reliability Testsupporting
confidence: 91%
“…Forcadell and Aracil (2017) argue that socially responsible business practices contribute to firm reputation. Moreover, several studies have demonstrated a positive association between CSR and firm reputation (Yan et al, 2022;Brammer and Pavelin, 2016;Gardberg et al, 2019;Khan et al, 2020a;Aggarwal & Saxena, 2023;Zhao et al, 2021;Cabrera-Luján et al, 2023). Further, Stakeholder theory guides organizations to prioritize the interests of diverse stakeholders, fostering ethical and responsible actions that enhance corporate reputation through positive relationships and aligned decisionmaking.…”
Section: Relationship Between Csr and Firm Reputationmentioning
confidence: 99%
“…We plan to ask also local people in the future research in several case studies. The next challenge for the future research for us is to focus on the impact of the socially responsible behaviour of agricultural holdings on their reputation, because a high level of CSR can help build the good name of the company (Aggarwal and Saxena 2023). This shall lead to the bet-…”
Section: Discussionmentioning
confidence: 99%
“…Corporate Social Responsibility (CSR) refers to how a company interacts with society. It encompasses a company's values and how they align with the expectations of the community in which the company operates (Aggarwal and Saxena 2022). McGuinness et al (2017) averred that the objective of CSR is to ensure that companies operate in a manner that is profitable and socially responsible.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%